Tax-benefit microsimulation model in developing countries: A feasibility study for an extension of SOUTHMOD in Indonesia - Arip Muttaqien; Denisa Sologon; Cathal O'Donoghue (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This study aims to expand the use of tax-benefit microsimulation tools in Indonesia. In particular, it reviews the feasibility of expanding SOUTHMOD, a tax-benefit microsimulation model being applied in developing countries that was developed based on the European Union tax-benefit microsimulation tool (EUROMOD) framework. First, the study reviews the tax and benefits system in Indonesia, followed by an explanation of possible data set and data requirements for simulation. Two potential sources of data are the fifth round of the Indonesia Family Life Survey and the National Socio-Economic Survey. Despite advantages and disadvantages to each, the results of the feasibility study show that both data sets could support the extension of the microsimulation model. This extension should be adjusted to the conditions of the data. For instance, we can focus on simulating indirect taxes, which are more relevant as they represent one of the core revenue sources in developing countries.
Keywords: H24; H71; O15; 330; EUROMOD; SOUTHMOD; microsimulation; Indonesia; tax-benefit